Growth suppression of bacteria by biofilm deterioration using silver nanoparticles with magnetic doping. Issue 48 (30th November 2022) - Torres-Mendieta, Rafael; Nguyen, Nhung H. A.; Guadagnini, Andrea; Semerad, Jaroslav; Łukowiec, Dariusz; Parma, Petr; Yang, Jijin; Agnoli, Stefano; Sevcu, Alena; Cajthaml, Tomas; Cernik, Miroslav; Amendola, Vincenzo
Abstract : Magnetic Ag nanoparticles are produced as ad hoc tools to disrupt biofilms formed by infectious bacteria permitting their efficient eradication. Abstract : Decades of antibiotic use and misuse have generated selective pressure toward the rise of antibiotic-resistant bacteria, which now contaminate our environment and pose a major threat to humanity. According to the evolutionary "Red queen theory", developing new antimicrobial technologies is both urgent and mandatory. While new antibiotics and antibacterial technologies have been developed, most fail to penetrate the biofilm that protects bacteria against external antimicrobial attacks. Hence, new antimicrobial formulations should combine toxicity for bacteria, biofilm permeation ability, biofilm deterioration capability, and tolerability by the organism without renouncing compatibility with a sustainable, low-cost, and scalable production route as well as an acceptable ecological impact after the ineluctable release of the antibacterial compound in the environment. Here, we report on the use of silver nanoparticles (NPs) doped with magnetic elements (Co and Fe) that allow standard silver antibacterial agents to perforate bacterial biofilms through magnetophoretic migration upon the application of an external magnetic field. The method has been proved to be effective in opening micrometric channels and reducing the thicknesses of models of biofilms containing bacteria such as Enterococcus faecalis, Enterobacter cloacae, and Bacillus subtilis . Besides, the NPs increase the membrane lipid peroxidation biomarkers through the formation of reactive oxygen species in E. faecalis, E. cloacae, B. subtilis, and Pseudomonas putida colonies. The NPs are produced using a one-step, scalable, and environmentally low-cost procedure based on laser ablation in a liquid, allowing easy transfer to real-world applications. The antibacterial effectiveness of these magnetic silver NPs may be further optimized by engineering the external magnetic fields and surface conjugation with specific functionalities for biofilm disruption or bactericidal effectiveness.